PENGARUH MOTIVASI DAN SISTEM REWARD TERHADAP KINERJA PEGAWAI PADA KEMENTERIAN AGAMA KABUPATEN MUSI RAWAS - Sumraini Sumraini; Abdullah Hehamahua (Jurnal Interprof, 2018)
The porpouse at the research are : 1) To knowed the influence motivation with the result at ministy of religion Musi Rawas District, 2) To knowed the reward system with the result at ministy of religion Musi Rawas District 3) To knowed the imfluence motivation and reward system with the result at ministy of religion Musi Rawas District. The result are 1) Motivation have with the result, so thitung is 21,190 and ttabel is 0,680 (value ttabel n = 44). To knowed the influenced reward with the result at ministy of religion Musi Rawas District, 2) The reward system have influence the reseult, its thitung is 21,190 dan ttabel is 0.680 (value ttabel n = 44) So The imfluence reward with the result at ministy of religion Lubuklinggau City 3) The imfluence competency and training with the result at ministy of religion Lubuklinggau City. So its Fhitung So its 5,703> Ftabel = 3,21